"A racial trust": Individualist, Eugenicist, and Capitalist Respectability in the Life of Roger Arliner Young. Issue 2 (1st October 2016) - Díaz, Sara P.
Abstract : Fifty years after her death, the professional experiences of Roger Arliner Young (1899–1964), the first black woman to earn a doctorate in zoology, continue to resonate with many women of color in the academy. Young's career trajectory was defined, in many ways, by the politics of respectability and its entanglements with other salient ideologies in the first half of the 20th century. Using several key moments in Young's life as an illustration, I argue that the historical context in which black respectability emerged was shaped by at least three specific ideologies—individualist, eugenicist, and capitalist—which leave an imprint on the politics of respectability. Because Young's career spanned multiple ideological contexts, from the racial uplift discourses in historically black colleges and universities, to the eugenicist nature/nurture debates within the biological sciences, to black capitalist economic separatism in Durham, her life demonstrates the diverse ways in which the politics of respectability regulated black women's engagement with the racial uplift project.